2013
DOI: 10.1371/journal.pone.0071742
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Sites at the 3’ Untranslated Region of the HLA-G Gene Are Associated with Differential hla-g Soluble Levels in the Brazilian and French Population

Abstract: HLA-G molecule has well-recognized tolerogenic properties, and the encoding gene shows lower frequency of polymorphism at the coding region but higher variability at regulatory 5’ and 3’ untranslated (3’UTR) regions. At least three 3’UTR polymorphic sites have been associated with HLA-G mRNA regulation, including the 14 base pair (14bp) Insertion/Deletion, +3142C-G and +3187A-G. We studied the association of polymorphic sites at 3’UTR (sequencing analysis, encompassing the 14bp Ins-Del/+3003T-C/+3010C-G/+3027C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
163
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(195 citation statements)
references
References 52 publications
18
163
3
9
Order By: Relevance
“…We found that the majority of donors with HLA-G low DC-10 carried haplotypes, such as UTR-2, UTR-5, UTR-7, containing 14bp Ins and G in position +3142, both variations previously associated with low mRNA stability. 10,14 These results are in line with a recent work showing that UTR-2 and UTR-5 are associated with low expression of soluble HLA-G. 48 The presence of G at position +3142 increases the affinity of miR-152, miR-148a, and miR-148b for mRNA, promoting the repression of HLA-G expression.14 Moreover, the over-expression of miR-148a or miR-152 in JEG-3 or LCL721.221 cell lines promotes post-transcriptional down-regulation of membrane-bound HLA-G. 49,50 Interestingly, analysis of the miRNome profile of DC-10 and its comparison with that of mDC identified ten differentially expressed miRNA, including miR-148a (Comi et al., unpublished data). Moreover, miR-152 was highly expressed in DC-10 as compared to CD14 + precursors.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We found that the majority of donors with HLA-G low DC-10 carried haplotypes, such as UTR-2, UTR-5, UTR-7, containing 14bp Ins and G in position +3142, both variations previously associated with low mRNA stability. 10,14 These results are in line with a recent work showing that UTR-2 and UTR-5 are associated with low expression of soluble HLA-G. 48 The presence of G at position +3142 increases the affinity of miR-152, miR-148a, and miR-148b for mRNA, promoting the repression of HLA-G expression.14 Moreover, the over-expression of miR-148a or miR-152 in JEG-3 or LCL721.221 cell lines promotes post-transcriptional down-regulation of membrane-bound HLA-G. 49,50 Interestingly, analysis of the miRNome profile of DC-10 and its comparison with that of mDC identified ten differentially expressed miRNA, including miR-148a (Comi et al., unpublished data). Moreover, miR-152 was highly expressed in DC-10 as compared to CD14 + precursors.…”
supporting
confidence: 76%
“…33,46 Only recently have these analyses been broadened to other polymorphisms in the 3'UTR region of HLA-G and to membrane-bound HLA-G. 47,48 In the present study, we screened the association of multiple variations in the 3'UTR HLA-G, considering alleles, genotypes, haplotypes, and diplotypes, with membrane-bound HLA-G expression on DC-10. We found that the majority of donors with HLA-G low DC-10 carried haplotypes, such as UTR-2, UTR-5, UTR-7, containing 14bp Ins and G in position +3142, both variations previously associated with low mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms mapped to the non-coding regions, particularly those in the 5' upstream regulator region (5' UTR) and 3' untranslated regions (3' UTR), reportedly influence the function of HLA-G molecules and have been implicated in some pathologies such as infertility, preeclampsia, failure in in vitro fertilization, and recurrent spontaneous abortion (RSA) (Menier et al, 2010;Donadi et al, 2011). Several studies have demonstrated the importance of the 3' UTR in the HLA-G expression profile (Rousseau et al, 2003;Martelli-Palomino et al, 2013). This region contains several regulatory elements, including a poly-A signal and AU-rich motifs involved in maintaining mRNA stability and isoform alternative splicing patterns, which may influence the function of HLA-G, particularly during pregnancy (Kovats et al, 1990;Fuzzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the 14-bp insertion allele was reported to be associated with low levels of both HLA-G mRNA and circulating soluble HLA-G (sHLA-G) isoforms (Chen et al, 2008;Boukouaci et al, 2011). It was also reported that plasma levels of sHLA-G were dramatically lower with the genotype +14-bp/+14-bp than with +14-bp/-14-bp and -14-bp/-14-bp genotypes (Chen et al, 2008;Martelli-Palomino et al, 2013). Thus, based on the results of several studies, the HLA-G molecule is considered to be a key player during early and mid-term pregnancy by contributing to the maintenance of gestation throughout pregnancy (Kovats et al, 1990;Rouas-Freiss et al, 1997;Fuzzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado está em concordância com outro estudo brasileiro, no qual a média de LTCD4+ foi de 339céls/mm³ dentre as participantes com HSIL e de 276,5céls/mm³ entre as mulheres com LSIL, assim como no presente estudo a número encontrado de LTCD4+ foi maior dentre as mulheres com lesões de alto grau, porém após análise de variância não foi encontrada associação entre o número de LTCD4+ com o grau de lesão cervical (P = 0,901) (ZIMMERNMANN et al, 2006). Embora não tenhamos encontrado associação entre as variáveis discorridas acima, sabemos que a prevalência da infecção pelo HPV está fortemente associada com a ocorrência de SIL e seu aumento está diretamente relacionado com a piora do grau da lesão cervical (MARKS et al, 2015NOWAKOWSKI et al, 2014 (LARSEN et al, 2013), entretanto em um outro estudo com mulheres brasileiras e francesas a frequência deste alelo foi de 43% na população brasileira (MARTELLI-PALOMINO et al, 2013). Em nossa amostra, não foi identificado associação entre a frequência do alelo inserção (P = 0,941), do alelo deleção (P = 0,938) ou dos genótipos (P = 0,993) e pertencer a algum dos grupos estudados, assim como ocorreu no já citado estudo africano, no qual também não foram encontradas diferenças dos genótipos entre os grupos HIV+ e HIV-(P = 0,56) (LARSEN et al, 2013).…”
Section: Análise Estatísticaunclassified